Potensi Dan Peluang Investasi Di Ibu Kota Nusantara Sesuai Peraturan Pemerintah Nomor 12 Tahun 2023 Tentang Pemberian Perizinan Berusaha, Kemudahan Berusaha, Dan Fasilitas Penanaman Modal Bagi Pelaku Usaha Di Ibu Kota Nusantara - Vita Gemina R (International Forum of Researchers and Lecturers, 2023)
This paper discusses the potential and opportunities for investment in Indonesia's new capital city, Nusantara, in relation to Government Regulation Number 12 of 2023 concerning the Granting of Business Licenses, Ease of Doing Business, and Investment Facilities for Business Actors in the Capital City of Nusantara (PP 12 of 2023). It will also discuss the property investment sector which is an investment opportunity for investors to invest in the Capital City of the Nusantara in phase I of 2022-2024. In addition, matters regulated in PP 12 of 2023 will also be presented in relation to investment arrangements in Indonesia as stipulated in Law Number 25 of 2007 concerning Investment.